MORРHOLOGICAL FEATURES OF THE MAXILLARY SINUS MUCOSA WITH INFLAMMATORY POLYCYSTIC CHANGES - Reshetniak, I.S.; Yeroshenko, G.A.; Bezeha, M.I.; Loburets, V.V.; Shevchenko, K.V. (World of Medicine and Biology, 2025)
The work identifies morphological features of polycystic changes in the mucous membrane of the maxillary sinuses of viral etiology. These cysts are not similar to previously known ones in terms of morphological features, so they can be considered as a separate type of cystic lesion of the paranasal sinus mucosa. The role of fungal etiology in the development of cystic changes is underestimated and requires further study.
Keywords: mucous membrane; maxillary sinuses; rhinosinusitis; polycystic changes